2011
DOI: 10.1111/j.1469-0691.2010.03350.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of co‐receptor usage of circulating viral and proviral HIV genome quasispecies by ultra‐deep pyrosequencing in patients who are candidates for CCR5 antagonist treatment

Abstract: UDPS combined with genotypic algorithms for prediction of HIV-1 co-receptor usage may provide quantitative data about the tropism of each variant present in the viral quasispecies. The aim of the present study was to assess co-receptor usage by ultra-deep pyrosequencing (UDPS), in comparison with the reference phenotypic test (Trofile), in patients who are candidates for CCR5 antagonist treatment, in both circulating and proviral HIV-1. Seventeen patients who were tested by Trofile were enrolled. UDPS of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
1
33
2
Order By: Relevance
“…However, standard genotypic test performed on bulk sequences may provide information only on the predominant circulating variants, whereas HIV-1 is present in each infected individual as a swarm of highly related variants referred to as quasispecies. We and others have recently reported that the classification obtained with the combined use of ultra-deep pyrosequencing (UDPS) with genotypic algorithms for prediction of HIV-1 coreceptor usage, such as position specific score matrix (PSSM) analysis or geno2pheno, is in good agreement with the standard phenotypic classification, and, in addition, may provide a detailed description of the viral HIV quasispecies, being able to quantify each variant with different coreceptor usage [19][20][21][22].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…However, standard genotypic test performed on bulk sequences may provide information only on the predominant circulating variants, whereas HIV-1 is present in each infected individual as a swarm of highly related variants referred to as quasispecies. We and others have recently reported that the classification obtained with the combined use of ultra-deep pyrosequencing (UDPS) with genotypic algorithms for prediction of HIV-1 coreceptor usage, such as position specific score matrix (PSSM) analysis or geno2pheno, is in good agreement with the standard phenotypic classification, and, in addition, may provide a detailed description of the viral HIV quasispecies, being able to quantify each variant with different coreceptor usage [19][20][21][22].…”
Section: Introductionmentioning
confidence: 83%
“…To maximize the genetic heterogeneity to be amplified and sequenced, for each sample, amplicons from at least four replicate PCR reactions were pooled, to analyze , for viral RNA, the viral heterogeneity present in 1 ml of plasma, and, for proviral DNA, that of associated with 2-6 Â 10 6 PBMC. To minimize the noise due to the high-throughput pyrosequencing platform, a correction pipeline, based on the translation of nucleotide sequences and conservation of only the coding ones, was adopted as previously described [20,21]. The application of this pipeline reduced the mean pyrosequencing error rate to 0.058%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Maraviroc (MVC) became the first, and so far only, FDA-approved smallmolecule HIV inhibitor/CCR5 antagonist for use in HIV-infected patients. Other CCR5 antagonists, agonists, and binding antibodies reached various stages of preclinical and clinical development but were eventually abandoned due to off-target complications (10), poor pharmacodynamics and pharmacokinetics (11), and difficulties in screening appropriate patients for treatment due to FDA requirements to counterscreen for CXCR4-using HIV-1 (12,13).…”
mentioning
confidence: 99%